Optimization of Cu/MnO catalyst for enhanced methane bi-reforming: A response surface methodology approach for sustainable syngas production - Irna Haslina, Ibrahim; Nor Shafiqah, Mohd Nasir; Nuremirah Syafiqah, Suhaimi; Li, Maoshua; Cuong Nguyen, Van; Sumaiya, Zainal Abidin (Taylor & Francis, 2024)
Hydrogen or syngas, valued for its clean and high-energy properties, stands as a promising solution to future energy shortages by converting CO2 and CH4 waste into renewable syngas through a reaction known as methane bi-reforming. Hence, the purpose of this current research is to examine the effectiveness of Cu/MnO2 catalyst in methane bi-reforming (MBR) using response surface methodology (RSM). The synthesis of the 15%Cu/MnO2 catalyst was accomplished using the ultrasonic impregnation method, followed by a comprehensive analysis and characterization of the catalyst using CO2-TPD, BET, H2-TPR, TPO, and XRD evaluation. The effect of reaction parameters was investigated using RSM analysis, including temperature, CO2/CH4 ratio, and gas hourly space velocity (GHSV) (700–900 °C, 0.2–1.0, and 16–36 L g cat−1 h−1, respectively). According to the analysis of variance and three-dimensional response surface plots, it was determined that CH4 conversion and H2 yield were largely influenced by temperature, whereas CO2 conversion and CO yield could be manipulated through CO2/CH4 feed ratio. Meanwhile, the GHSV appeared to have a significant influence on the H2/CO ratio and CH4 conversion. From the experimental data, it was found that the 15%Cu/MnO2 catalyst performed best under specified optimal conditions of 800 °C, a CO2/CH4 ratio of 0.6, and a GHSV of 26 L g cat−1 h−1. These optimal conditions resulted in the maximum conversion of CH4 (54.67%), CO2 conversion (47.52%), H2 yield (43.81%), CO yield (36.29%), and H2/CO ratio (1.384). Despite the inevitability of carbon formation resulting from the breakdown of CH4 and CO at high temperatures, the examination of the spent catalysts under optimal conditions yielded a smaller quantity of carbon of approximately 28.27% in comparison to the suboptimal conditions with 55.37%.